FORMULATION AND IN VITRO CHARACTERISATION OF GLUCOSE-RESPONSIVE NANOCAPSULES FOR THE DELIVERY OF M-INSULIN - VISHWAKARMA, NIKHAR; VYAS, SURESH P. (International Journal of Applied Pharmaceutics, 2023)
Objective: The present study aimed to develop and characterize Chitosan coated Alginate Nanocapsules loaded with M-Insulin Concanavalin A Complex for glucose-responsive delivery. Methods: Preformulation studies were performed on the Insulin human recombinant and the Nanocapsules were prepared by the ionic gelation method and coated with chitosan using electrostatic attraction. The formulation variables were optimized using Box-Behnken design (BBD) with the help of Design-Expert® Software. Three independent variables taken were the concentration of chitosan (A1), the concentration of sodium alginate (A2), and the stirring rate (A3). The response variables selected were the average particle size (nm) (B1), polydispersity index (B2), and cumulative release (%) (B3). Results: The results from the Preformulation studies indicated that the received sample of the Insulin human recombinant was pure. The optimized nanocapsules possessed an average particle size of 382.4 nm, PDI 0.211 and zeta potential of 30.25 mV. The entrapment efficiency was found to be 79.2 %. The nanocapsules were further characterized for their surface morphology using TEM and were found to be of regular shape. The in vitro drug release study indicated that the nanocapsules were able to release 58 % of M-insulin in hyperglycaemic conditions for 12 h. Conclusion: The outcomes of the study demonstrated that the developed nanocapsules can be effectively used for glucose-responsive delivery of M-insulin.